Evaluation of transfusion transmitted infections and distribution of ABO and Rh blood groups in donors in Eastern Turkey - Ekinci, Ömer; Kara, Osman; Demircioğlu, Sinan; Dogan, Ali; Merter, Mustafa; Gurbuz, Ali Fuat; Demir, Cengiz (My University, 2019)
Aim: Knowledge of blood group distribution and blood serology in a given region is critical for the proper functioning of blood banksand also for delivering the blood products to need owners. We aimed to determine the distribution rates of ABO and Rh blood groupsand the incidence of transfusion-transmitted infections in the healthy donors in our region.Materials and Methods: A total of 108,368 healthy individuals were participated in this study. Incidence of HBsAg, anti-HCV, anti-HIV-1/2 and syphilis along with blood group distribution were evaluated retrospectively.Results: Of the blood donors, 98,901(% 91.24) were male and 9,467 (%8.76) were female. Frequency of O, A, B, and AB blood groupdistribution in the donor population were 31.2%, 44.0%, 16.2%, and 8.6%, respectively. Of the blood donors, 95,039 (87.7%) were Rhpositive and 13,229 (12.3%) were Rh negative. A total of 1,685 donors (1.55%) tested positive for HBsAg, 102 (0.09%) for anti-HCV, 23(0.022%) for anti-HIV-1/2, and 58 (0.05%) tested positive for syphilis.Conclusion: The ABO and Rh blood antigens distribution rates found in our study were similar for male and female and resembledthe overall rates for Turkey. When looking at the annual analysis of the donor group, we observed a significant decrease of HbsAgtest positivity over a seven-year-period (p values for time periods 2008-2009, 2010-2011, 2012-2013, 2014-2015 were 0.016, 0.02,0.001, and 0.003 respectively). We believe that our results will be useful for the creation of a database on blood group distributionand the seroprevalence of infectious agents.
Keywords: Halk ve Çevre Sağlığı; Mikrobiyoloji; Hematoloji; Tıbbi Laboratuar Teknolojisi